Impact of Financial Development on CO2 Emissions: Panel Data Evidence from Iran's Economic Sectors - Naghmeh Ghorashi; Abbas Alavi Rad (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The national trend indicates that various provinces of Iran have experienced in attaining economic growth exclusive of parallel observing a boost in CO2 emissions. It is clear that the effects of CO2 emissions on health indicators such as death rate, infant mortality, and health expenditures have been ignored by policy makers over the last decade.   Methods: This study for the first time in previous literature in Iran, utilizes 1989-2016 panel data of the three economic sectors (agriculture, industry and services) of Iran to examine the effect of financial development on CO2 emissions using Pooled Mean Group (PMG) and Mean Group (MG) Regression techniques. The potential impact of government size and capital stock on CO2 emissions is also analysed.   Results: According to empirical results, in the long-run, government size and capital stock increase CO2 emissions, while financial development compact it. However, the results show these variables don’t have statistically significant effect on CO2 emissions in short-run.   Conclusion: The study opens up new policy insights to control the Environment from degradation by financial development on economic sectors. It recommends that policy makers should realize the potentiality of the financial development in minimizing the CO2 emissions. Therefore, the policy makers need to facilitate more financing at lower costs for investment in environmental projects.